18F-FDG PET/CT versus conventional investigations for cancer screening in autoimmune inflammatory myopathy in the era of novel myopathy classifications. Issue 4 (April 2019) - Maliha, Peter G.; Hudson, Marie; Abikhzer, Gad; Singerman, Julia; Probst, Stephan
Abstract : Background: To compare the performance of fluorine-18-fluorodeoxyglucose ( 18 F-FDG) PET/computed tomography (CT) and conventional tests for cancer screening in autoimmune inflammatory myopathy (AIM) patients. Patients and methods: We carried out a retrospective cohort study of AIM patients from one academic center in Montreal, Canada, classified using myositis-specific antibodies, who underwent 18 F-FDG PET/CT between April 2005 and February 2018 and were followed up on average 3.5±2.4 years. Patients were excluded if follow-up was insufficient, AIM diagnosis was indeterminate, and/or malignancy was diagnosed before an 18 F-FDG PET/CT scan. Demographic/clinical data, 18 F-FDG PET/CT results, and available conventional screening tests results were retrieved from electronic and paper medical records. Results: 100 18 F-FDG PET/CT studies in 63 unique patients [31/63 dermatomyositis (DM), 25/63 overlap myositis, 1/63 inclusion body myositis, 1/63 polymyositis, 1/63 orbital myositis and 4/63 unspecified myositis] were evaluated. Three patients, all classified as DM, were diagnosed with cancer during follow-up with conventional cancer screening tests: breast cancer detected by mammography; squamous cell carcinoma of the skin detected by physical examination; and multiple myeloma detected by blood work. 18 F-FDG PET/CT did not detect any malignancy and led to more additional biopsies than conventional screening (8 vs. 5). Conclusion: 18 F-FDG PET/CT does not appear to be useful in cancer screening for AIM patients compared with conventional screening and carries potential harms associated with follow-up investigations. The risk of cancer in AIM differs by myositis-specific antibodies-defined subsets and cancer screening is likely to be indicated only in high-risk patients, particularly DM. These results, replicated in larger, multicentered studies, may carry significant consequences for optimal management of AIM and health resource utilization.